A scoping review of middle managers in the digital transformation era in public sector organizations: are they still needed? - Sigit Kusmaryanto; Claudius Budi Santoso (Cogent Business & Management)
Middle managers play a crucial role in the success or failure of digital transformation programs and are themselves targets of change, particularly in public sector organizations. As intermediaries, they occupy ambiguous, complex, and paradoxical roles, with digital technology often perceived as diminishing their necessity. This study examines the relevance of middle managers in the digital transformation era within public institutions through a scoping review, following a six-stage framework to ensure rigor and transparency. Literature was sourced from databases such as Scopus, EBSCOhost, BASE, Google Scholar, and other search techniques, resulting in 33 works from 1990 to 2023 that met the inclusion criteria. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and assessed study quality using the Mixed Methods Appraisal Tool (MMAT). The findings indicate a range of middle manager responses to digital transformation, varying from positive to negative, though many feel increasingly empowered and essential to organizational success. Digitalization reshapes their competency and training needs. This study provides practical insights for empowering middle managers in the public sector and suggests avenues for future research within modern public administration contexts.